Physiologic quality of carioca bean seeds stored in different environments - Zucareli, Claudemir; Brzezinski, Cristian R.; Abati, Julia; Werner, Flavia; Ramos Junior, Edison U.; Nakagawa, Joao [UNESP] (Univ Federal Campina Grande, 2015)
The aim of the study was to evaluate the physiologic quality of lots of seeds of bean cultivars of carioca during storage in different environments. The study was conducted at the State University of Londrina, in a completely randomized design with four replications in a 3 x 2 x 4 factorial design, with three lots of cultivars of common bean (lot 1: Carioca Prococe, lot 2: IAC Carioca Tibata and lot 3: IAC Carioca), two storage environment (natural environment and dry chamber) and four storage times (0, 6, 12, and 18 months). Seed quality was evaluated by the following tests: water content, first count of germination, germination, accelerated aging, electrical conductivity and seedling emergence in the field test. Data were subjected to analysis of variance and comparisons of means by Tukey test at 0.05 probability and regression analysis. Seeds of beans of the lot 1 (Carioca Precoce) and lot 3 (IAC Carioca) had better physiologic quality against lot 2 (IAC Carioca Tibata). The physiologic quality of seeds of beans is reduced during storage in all lots, but with steeper rates under uncontrolled temperature and humidity conditions.
Keywords: Phaseolus vulgaris L.; germination; vigor; dry chamber; natural environment